The Nexus of Profitability and Leverage on Company Cash Holdings: Case Study of Banking Companies Listed on Indonesia Stock Exchange - Reillo Subaktio; Candra Hakiki; Habibah Habibah; Febby Angelina (eCo-Fin, 2025)
Cash holding is important for businesses, including those in the banking sector for operational needs and financial health. This study aims to analyse the effect of profitability and leverage on the cash holding of banking companies listed on the Indonesia Stock Exchange. This study aims to analyse the effect of profitability and leverage on the cash holding of banking companies listed on the Indonesia Stock Exchange. This study uses secondary data on banking companies listed on the Indonesia Stock Exchange and the sample of this study was 43 banking companies with an observation period from 2014 to 2017. The research method used statistics analysis a simultaneous test (t-test) with panel data regression analysis. The results of this study indicate that profitability has a positive but insignificant effect on the company's cash holding. However, leverage has a negative but insignificant effect on cash holding. The policymakers should investigate the specific conditions under which leverage impacts cash holding to develop targeted policies. Therefore, policies could encourage companies to prioritize cash holdings over external funding.